Efikasi Diri Pengambilan Keputusan Karir pada Mahasiswa Tingkat Akhir: Bagaimana Peran Dukungan Orang Tua dan Teman Sebaya? - Alzena Graziella; Retno Sulistiyaningsih (Jurnal Pendidikan Indonesia, 2026)
Final-year students often experience confusion in determining their future careers, resulting in low Career Decision Making Self-Efficacy (CDMSE). In fact, CDMSE plays an important role in building self-confidence to plan and make career decisions. Parental and peer support are known to be associated with increased CDMSE. This study aims to analyze the influence of parental and peer support on CDMSE among final-year students. The research sample consisted of 400 final-year students, selected using convenience sampling. Data collection was conducted through Google Forms distributed via social media. The research instruments included three scales: parental support scale (15 items, α=0.903), peer support scale (17 items, α=0.896), and CDMSE scale (18 items, α=0.903). Data analysis was performed using correlation and regression statistical tests to examine the partial and simultaneous effects between variables. The results showed that parental support had a significant partial effect on each dimension of CDMSE, namely self-assessment, job information, goal selection, planning, and problem solving. Peer support also had a significant partial effect on all dimensions of CDMSE. Simultaneously, parental and peer support significantly influenced the CDMSE as a whole. These findings confirm that social support from parents and peers plays an important role in increasing final-year students' confidence in making career decisions.